Exploring staff clinical knowledge and practice with LGBT residents in long-term care: a grounded theory of cultural competency and training needs - Donaldson, Weston Verlaine, author; Vacha-Haase, Tammi, advisor; Davalos, Deana, committee member; Swaim, Randall, committee member; Wood, Wendy, committee member (Colorado State University. Libraries, 2014)
Providing culturally competent care to LGBT residents is an important area of concern in the current practice of long-term care (LTC) staff and providers. Existing literature shows that LGBT residents are likely to face discrimination and suboptimal care in LTC facilities due to homophobia, transphobia, and heteronormative/cisnormative policies. This grounded theory study assessed the LGBT cultural competency that exists among staff working in LTC facilities, and provides a framework for understanding how their knowledge, skills, and attitudes with respect to LGBT residents are connected to their ability to care for those populations. The core category identified in this study was "staff sensitivity to minority sexual orientation and gender identity (SOGI) of residents." Main categories reflected the ways that competency, awareness, knowledge, experience with LGBT people, attitudes toward LGBT people, and current training needs reflect staff sensitivity to resident SOGI. Recommendations are made for training LTC staff to be sensitive to the particular needs of sexual and gender minorities in their facilities.
Keywords: cultural competency; long-term care; LGBT; grounded theory